Seroprevalence of SARS-CoV-2 among Health Care Personnel in Portugal - Álvaro de Carvalho; Ana Virgolino; José Germano de Sousa; Henrique Barros; Miguel Guimarães; Francisco Antunes (Medical Sciences Forum, 2021)
Health care personnel (HCP) might be highly exposed to SARS-CoV-2 infection. This study aims to determine the seroprevalence of SARS-CoV-2 among HCP in Portugal. A cross-sectional study was conducted between 1 June and 19 July 2020, following the first wave of COVID-19 in the country, with a convenience sample of HCP from different Portuguese health care units, geographically distributed at the national level. Diagnosis of COVID-19 was an exclusion criterion. HCP were tested for IgG antibodies against SARS-CoV-2. Data regarding participants’ demographic characteristics, medical history, COVID-19 symptoms, previous clinical testing for acute SARS-CoV-2 infection and Personal Protective Equipment (PPE) practices while caring for patients in areas with COVID-19 patients were also recorded. A total of 1802 HCP were screened (80.9% women), of which 55 (3.1%) had positive test results for SARS-CoV-2 antibodies. Factors such as geographical distribution (p = 0.002), profession (p = 0.018), having had a family member with COVID-19 (p < 0.001) and having had contact with family members with COVID-19 (p = 0.003) were found to be associated with infection. Adjusting for gender, age group, regional health administration and size of the household, health care assistants have an increased risk of having a positive SARS-CoV-2 test result in comparison to nurses. Understanding the prevalence of and factors associated with SARS-CoV-2 infection among HCP is important for developing effective strategies to protect them and their patients.